2020
DOI: 10.3998/mjcsloa.3239521.0026.110
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Impact of an International Service-Learning Project through Community Assessment in Rwanda

Abstract: In 2015, a university from Hong Kong led an international service-learning course to Kigali, Rwanda. The focus of the course was to install solar panels in individual households in a community, on the outskirts of Kigali, without access to electricity. The following year, the Hong Kong university partnered with a university in the United States and returned to Rwanda to expand the solar panel project in the same community. The central question of the qualitative impact assessment was, How, if at all, has the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…However, the plethora of research with an overemphasis on students’ learning outcomes continue to provide a one-sided view of the impact of service-learning, thus, presenting the notion that service-learning offers more benefits to students than communities (Beran & Lubin, 2012). Given the conceptualization of service-learning as a pedagogical practice that provides mutual beneficial outcomes to students and communities, further analysis of the effects of service-learning on communities should be explored (see Spear & Chapman, 2020). As evidential findings indicate, studies on the effects of service-learning to communities are limited in comparison to research on student outcomes, and while it is assumed that service-learning offers positive benefits to community organizations (Karasik, 2020; Vizenor et al, 2017), community partners’ perspective of service-learning has received less attention (Bennett et al, 2016; Gerstenblatt, 2014; Stanton & Giles, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the plethora of research with an overemphasis on students’ learning outcomes continue to provide a one-sided view of the impact of service-learning, thus, presenting the notion that service-learning offers more benefits to students than communities (Beran & Lubin, 2012). Given the conceptualization of service-learning as a pedagogical practice that provides mutual beneficial outcomes to students and communities, further analysis of the effects of service-learning on communities should be explored (see Spear & Chapman, 2020). As evidential findings indicate, studies on the effects of service-learning to communities are limited in comparison to research on student outcomes, and while it is assumed that service-learning offers positive benefits to community organizations (Karasik, 2020; Vizenor et al, 2017), community partners’ perspective of service-learning has received less attention (Bennett et al, 2016; Gerstenblatt, 2014; Stanton & Giles, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature suggested that best practice for the long-term success of international service learning could be facilitated through reciprocal relationship between the overseas institutes and the local community. 34 For the future implementation, the development of a systematic metric in measurement of the impact of international service on students could be proposed to improve their clinical thinking skills and global citizenship. Conducting the metrics such as Cultural Intelligence Scale and Global Citizenship Scale with the dimensions of social responsibility would be beneficial to this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the current literature, the relationship between Service Learning and Kohlberg’s theory of moral education is limited mostly to research that attempts to show how participation in Service Learning programs affects moral development, sometimes using developmental measurements inspired by Kohlberg (e.g. Bernacki and Jaeger, 2008; Coquyt, 2020). According to Hare, however, these studies barely scratch the surface of the matter.…”
Section: Conclusion: Educating In a Democratic Ethos From A Renewed P...mentioning
confidence: 99%